Fostering vocabulary enhancement through language games in the context of blended learning environment - Malissa Maria Mahmud, * (2015)
Numerous obstacles inhibit English as Second Language (L2) learners from grasping new vocabulary; nonetheless, one of the major challenges is the nominal time devoted to vocabulary instruction. Predominantly, semantic and conceptual relationships could augment cognitive skills and in turn, develop reading comprehension and writing proficiency. However, conventional vocabulary learning such as rote learning seems likely to further diverge the controversy over language learning, in which linguists-technologists are squared off against memorization technique, in which students are encouraged to remember the vocabulary through repetition often without having to understand the reasoning or relationships involved. This research is carried out to introduce games as an apparatus in a hybrid learning environment where students participated with their peers to develop a self–regulated approach to vocabulary enhancement. The aims on the efficacy of vocabulary learning through vocabulary games for L2 Learners was proved to be accurate based on the results obtained from the experiment conducted. It was also observed that from the three vocabulary games, homonyms helps is the most effective in increasing vocabulary learning for L2 learner compared to crossword puzzle and wordsearch.